Strategi Komunikasi Pemasaran Society Coffee House Purwokerto Melalui Media Sosial - Kurnia, Risma Eka; Sulaiman, Adhi Iman; Runtiko, Agus Ganjar (LPPM Institut Pendidikan Nusantara Global, 2025)
This research analyzes the marketing communication strategies used by Society Coffee House in Purwokerto, focusing on how digital media, specifically Instagram, contributes to brand visibility and consumer engagement. With the rapid increase of coffee shops in the region, Society Coffee House has maintained its position by leveraging various marketing tools. This study employs qualitative methods, including interviews with owners, employees, and consumers, as well as observations and secondary data. Findings show that strategic use of social media, brand positioning, and customer loyalty programs have been key to maintaining competitiveness. The research also suggests that further integration of digital marketing tools and consumer interaction could enhance their market position.